2019
DOI: 10.1007/s10552-019-01256-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and serum metabolite concentrations in young women

Abstract: Purpose: Alcohol consumption is an established breast cancer risk factor, though further research is needed to advance our understanding of the mechanism underlying the association. We used global metabolomics profiling to identify serum metabolites and metabolic pathways that could potentially mediate the alcohol-breast cancer association. Methods:A cross-sectional analysis of reported alcohol consumption and serum metabolite concentrations was conducted among 211 healthy women 25-29 years old who participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…One pathway by which the production of steroid hormones can be controlled is by the hypothalamic-pituitary-adrenal (HPA) axis [ 30 ]. Alcohol stimulates the HPA axis, which might explains the positive association between alcohol and these two metabolites [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One pathway by which the production of steroid hormones can be controlled is by the hypothalamic-pituitary-adrenal (HPA) axis [ 30 ]. Alcohol stimulates the HPA axis, which might explains the positive association between alcohol and these two metabolites [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…After drying, sample extracts were reconstituted in solvents compatible with each of the four analytical methods. Details of the methods have been reported previously [18,19]. Briefly, two aliquots were analyzed under acidic positive ion conditions using a C18 column.…”
Section: Metabolomics Assaysmentioning
confidence: 99%
“…Altered levels of sarcosine in serum/plasma and urine have been observed in several diseases, such as type 2 diabetes 62 64 , narcolepsy 65 , allergic rhinitis 66 , chorioretinopathy 67 , and even in healthy persons in response to exercise 68 or in association with alcohol consumption 69 . Walters et al 70 showed in plasma from rats and humans that sarcosine is reduced with ageing and elevated by dietary restriction.…”
Section: Resultsmentioning
confidence: 99%